Developing a mitral valve center of excellence. (March 2018) - El-Eshmawi, Ahmed; Castillo, Javier G.; Tang, Gilbert H.L.; Adams, David H.
Abstract : Purpose of review: Despite the proven superiority of mitral repair over replacement for degenerative mitral disease, mitral valve replacement remains common. Guidelines now recommend referral of patients, particularly those whom are asymptomatic, to valve centers of excellence, although criteria that define such centers remain to be established. The purpose of this review is to define the structure of a mitral center of excellence and to review current clinical outcomes which are possible in such a center. Recent findings: Recently, American College of Cardiology/American Heart Association as well as the European Society of Cardiology/European Association of Cardiothoracic Surgery guidelines define mitral centers of excellence as either centers in which the likelihood of successful and durable repair exceeds 95% and with an operative mortality risk of less than 1% (American College of Cardiology/American Heart Association definition) or centers with high repair rates, low operative mortality, and a record of durable results (European Society of Cardiology/European Association of Cardiothoracic Surgery definition). There is however less clarity about the structure and function of a center that achieves these outcomes. Summary: The importance of centers of excellence in mitral valve surgery are now well recognized, and this review will highlight the key components and outcomes of an established mitral valve reference center.